The dark and bright sides of hubris: Conceptual implications for leadership and governance research. (December 2019) - Zeitoun, Hossam; Nordberg, Donald; Homberg, Fabian
Hubris among corporate leaders has recently gained much academic attention, with strategy and corporate governance research focusing mainly on negative aspects, such as overreach by strategic leaders during acquisitions. However, adjacent disciplines including entrepreneurship and innovation identify positive consequences too. How comparable are these findings? Appraising the conceptual and methodological approaches, we find that while the hubris concept has many strengths, several challenges remain. We suggest conceptual and empirical research directions aimed at increasing construct clarity, validating the hubris construct and extending the scope of hubris research. We also propose that research with boards and top management teams can help clarify how they make decisions to cope with the 'dark side' of hubris without suppressing 'bright side' outcomes.